Characterization of secretory structures and essential oils in aerial parts of torch ginger [Etlingera elatior (Jack) R.M. Sm.] at different developmental stages - Lee, Yee Ling (2019)
Torch ginger (Etlingera elatior) is an aromatic plant popularly used as flavouring in food preparation. It has been a subject for many scientific studies aimed at investigating their chemical composition of the essential oils (EO). However, the lack of systematic analysis involving different plant parts and developmental stages may have contributed to variation on the major compounds reported by different groups of researchers. Furthermore, identification on the type of secretory structures responsible for accumulating and storing the EO have not been carried out hitherto. Therefore, this study was carried out to address the current research gaps. First, the presence of secretory cells, glandular and non-glandular trichomes were microscopically identified as the main secretory system for EO of torch ginger. The discovery of glandular trichomes is the first report on the EO secretory structure in Zingiberaceae. The histochemical tests indicated the secretory contents of the secretory structures comprised of terpenes and lipophilic that are typical characteristic of EO. Second, the variation in chemical composition of aerial parts (leaves, peduncle and inflorescence head) of torch ginger at different developmental stages were analysed using GC-MS. The EO leaves from different position were also sampled repeatedly at 8 and 18 WAE to study the changes in EO content. The EOs in leaves, peduncle and inflorescence head were predominated by 1-dodecanol and n-dodecanal as the two major compounds irrespective of developmental stages. However, the α-pinene content influenced markedly on the EO in inflorescence head and peduncle during the initial stage of flowering (10.9 and 21.1%, respectively), which then decreased substantially in the following stages (content ranged between 0.3 to 0.7%; and 0.4 to 4.1%, respectively). Subsequent multivariate analysis using principal component analysis (PCA) was able to distinguish the differences among the EO samples. Most notably, α-pinene was identified as the key compound that characterized the EO in inflorescence head, while n-dodecanal, 2-undecanone and tetradecanoic acid were the key characterizing compounds in the peduncle. Finally, the antioxidant activities of the EO were evaluated using 1,1-diphenyl-2-picrylhydrazil (DPPH) radical scavenging assay and β-carotene bleaching method. Partial Least Squares (PLS) were employed to correlate the antioxidant activities and the chemical compositions of EO. The leaves at 18 WAE and peduncle at tight bud stage exhibited potent radical scavenging and inhibitory activities. Sesquiterpenes ((E)-β-farnesene, α-humulene and β-elemene) and monoterpenes (α-pinene and α-terpineol) were correlated as the active compounds that contributed towards the antioxidant activities. On the other hand, the inflorescence head at full bloom stage was shown to be potent inhibitory activities compared to radical scavenging with (E)-caryophyllene, (E, E)-α-farnesene, n-dodecanal and 1-dodecanol correlated as the active compounds. In summary, the findings were able to establish the variation in chemical composition of torch ginger as a function of plant developmental stages and their implication on the antioxidant activities.